Промачивание слоистого грунта с образованием на его поверхности слоя воды - Поляков, В.Л. (Видавничий дім "Академперіодика" НАН України, 2007)
The task of intensive inﬁltration for multilayer soil due to a severe rainfall taking into account ponding is formulated. A number of formulae are obtained to calculate the water depth H of the surface layer, position of the water saturation front, and surface intake rate at a constant precipitation. The analysis of several factors which afect the depth H is performed.